Knowledge of nurses on benefits of the method kangaroo mother: neonatology service. Sergio Bernales Hospital, Comas, Lima - Salas-Ordoño, Albina (2019)
The present work had as objective to determine the degree of relationship that exists between the level of knowledge and practices of nurses on the benefits of the Kangaroo Mother Method in the neonatology service at Sergio Bernales Hospital from January to December in 2012; so that, it was applied a descriptive correlational design, to describe and associate the knowledge of control and practices of nurses on the benefits of the Kangaroo Mother Method. It is raised the following hypothesis there is significant relationship between knowledge and the practice of nurses on the benefits of the Kangaroo Mother Method in the Neonatology Service of Sergio E. Bernales Hospital in commas - Lima 2012. The population was 25 nurses working at the Neonatal Intensive Care Unit, the applied sampling is not random, and by the accessibility is considered all the nurses that there is in the population. The results show that there is a significant relationship between knowledge and the practices of nurses related to the guidance given to the patient on the early stimulation of prematurity with the Kangaroo Mother Method in the Neonatology Service of Sergio E. Bernales Hospital in Comas - Lima. The limitations were economic since it was settled by the author, as well as the existence of few professionals with the time available to provide the information and scant bibliography on the topic.